The rationality of rukhshah in social activities: Reviewing the ability of jama’ prayer for carnival participants in the perspective of ulama 4 madzhab - Muhammad Ma'aliyal Umur; Ahmad Fakk Dominika Taqi Aha Putra; Najmi Nahdin Afkari; Muhammad Izul Haq; Manarul Alam Al Farizi (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
This study analyzes the combination of prayer (jama’ sholat) for carnival participants and workers in the framework of classical and contemporary fiqh. The purpose of the study was to evaluate whether carnival activities meet the criteria of masyaqqah syadidah (severe difficulty) that justify the application of rukhshah (legal concessions) in the perspective of the four main schools (Hanafi, Maliki, Shafi’i, and Hanbali) as well as the views of contemporary scholars. This research offers novelty by examining the incorporation of prayer in the context of carnival, which is a contemporary social phenomenon that has not been widely discussed in fiqh literature. Previously, most fiqh studies on rukhshah focused more on travel or emergency conditions, while this study explored the application of rukhshah in the context of recreational and professional activities, such as carnivals. Using qualitative research methods, this study analyzed classical fiqh texts, scientific articles, and related academic literature. The main findings show that carnival, as a voluntary recreational activity, does not meet the criteria of udzur syar’i to incorporate prayer. The majority of scholars prohibit the combination of prayers without a valid reason such as travel or emergency conditions. However, exceptions may apply to carnival workers who are professionally bound and risk economic harm if they leave duty, provided that this practice does not become the norm. In conclusion, although rukhshah is acceptable in limited cases, carnival activities do not justify the incorporation of prayers in general. This study highlights the need for good time management to fulfill prayer obligations without sacrificing work or social activities.